Penerapan Metode Bernyanyi pada Pembelajaran Bahasa Arab di Kelas I SD Al-Amin Cemani Grogol Sukoharjo Tahun Ajaran 2022/2023 - Novita Isnaeni (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2023)
This study aims to describe the implementation of the singing method in Arabic language learning in class Ic of SD Al-Amin Cemani Grogol Sukoharjo. In addition, this research also aims to identify the strengths and weaknesses of the singing method in Arabic learning. The research uses a descriptive qualitative approach. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis followed the technique proposed by Miles and Huberman, which includes: data reduction, data display, and drawing conclusions/verification. The validity of the data was checked using triangulation techniques. The results of the study show that the implementation of the singing method in Arabic language learning in class Ic of SD Al-Amin Cemani Grogol Sukoharjo made it easier for students to understand the material delivered by the teacher. This method also increased students’ enthusiasm and motivation in learning.